Industrial Ecology in support of building a Circular Economy - Korevaar, Gijsbert (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
Circular economy and industrial ecology mark different concepts that both support the transition to a sustainable society. Industrial symbiosis, one of the main tools in the field of industrial ecology, can support a successful circular economy, because of its focus on industrial networks and clusters.